Climate Conditions During a Rift Valley Fever Post-epizootic Period in Free State, South Africa, 2014–2019 - Anyamba, Assaf; Damoah, Richard; Kemp, Alan; Small, Jennifer L.; Rostal, Melinda K.; Bagge, Whitney; Cordel, Claudia; Brand, Robert; Karesh, William B.; Paweska, Janusz T. (Frontiers in Veterinary Science, 2022)
Rift Valley fever virus (RVFV) activity in Southern Africa tends to occur during periods of sustained elevated rainfall, cooler than normal conditions, and abundant vegetation cover creating ideal conditions for the increase and propagation of populations of RVFV mosquito vectors. These climatic and ecological conditions are modulated by large-scale tropical-wide El Niño–Southern Oscillation (ENSO) phenomena. The aim of this 5-year study was to investigate climatic conditions during Rift Valley fever “post-epizootic ” period in Free State province of the Republic of South Africa, which historically experienced the largest RVF outbreaks in this country. We collected satellite-derived rainfall, land surface temperature (LST), and normalized difference vegetation index (NDVI) data since 2014 to understand broad environmental conditions in the years following a period of sustained and widespread large RVF outbreaks (2008-2011) in the region. We found this post-epizootic/ interepizootic period to be characterized by below-normal rainfall (~-500 mm), above LSTs (~+12 oC), depressed NDVI (60% below normal), and severe drought as manifested particularly during the 2015-2016 growing season. Such conditions reduce the patchwork of appropriate habitats available for emergence of RVFV vectors and diminish chances of RVFV activity. However, the 2016-2017 growing season saw a marked return to somewhat wetter conditions without any reported RVFV transmission. In general, the aggregate vector collections during this 5 year period follow patterns observed in climate measurements. During the 2017-2018 growing season, late and seasonally above average rainfall resulted in a focal RVF outbreak in one location in the study region. This unanticipated event is an indicator of cryptic RVF activity during post-epizootic period and may be a harbinger of RVFV activity in the coming years.